Determining the Effect of Heat Stress on Meat Quality of Controlled Atmospheric Gas Stunned Broilers - Galo A., Nohelia S. (Zamorano: Escuela Agrícola Panamericana, 2025)
Animal welfare has gained significant importance in poultry production particularly with adoption of Controlled Atmospheric Gas Stunning. Three trials were conducted. A completely Randomized Design was used, with a 2x2 factorial arrangement, evaluating two factors, temperature (17 °C and 30 °C) and time (5 and 7 minutes). This resulted in 4 treatments combinations: 5 minutes cold (at 17 °C), 7 minutes cold (at 17 °C), 5 minutes hot (at 30 °C), and 7 minutes hot (at 30 °C). For the statistical analysis, the data was evaluated using LSMEANS to examine the interaction between the factors of time and temperature across the treatments, with Tukey's (HSD) test using the SAS Program at p<0.05. Results showed no significant differences in woody breast myopathy and weight across treatments. There was a significant difference in the pH values, with the highest pH observed in the 7 minutes hot (at 30°C) treatment with (6.43 ± 0.34) and the lowest in the 5 minutes cold (at 17 °C) treatment with (6.29 ± 0.41). Significant differences were found in lightness (L*) and redness (a*), but not in yellowness (b*) indicating that time and temperature influenced meat color characteristics. Cooking loss was highest in the 7 minutes hot treatment (31.12± 10.48), and the lowest in the 5 minutes cold treatment (20.03 ± 6.24), indicating greater moisture loss at higher temperatures. Drip loss showed no significant differences. In the texture analysis there were significant differences in force values, 7 minutes hot had the highest force (224.72 ± 165.62), and 5 minutes cold had the lowest value (154.92 ± 123.71).